Comparison of antihypertensive efficacy of carvedilol and nebivolol in mild-to-moderate primary hypertension: a randomized trial - ERDOĞAN, OKAN (AVES YAYINCILIK, 2011)
Objective: The aim of the present study is to compare the antihypertensive effects of carvedilol and nebivolol in mild to moderate hypertensive patients. Methods: It is a prospective; placebo-controlled, cross-over, double-blind, randomized, single-center clinical trial. Patients (n=20) who were first diagnosed with mild to moderate systemic hypertension according to mean ambulatory blood pressure measurements > 130/85 mmHg and no previous antihypertensive therapy were prospectively enrolled into the study. After 10 days of placebo run-in period, they were randomized within the same group as cross-over design to one month carvedilol 25 mg and one month nebivolol 5 mg regimen given once daily in the morning. The primary outcome variables were systolic and diastolic blood pressures determined by 24-hour ambulatory blood pressure measurements. Mutlivariate analysis of variance for repeated measurements with 3x2 factorial design was used for statistical analysis of results. Results: The study group consisted of 6 women and 14 men whose mean age was 42.9 +/- 12.8 years (range 19-63 years). Mean heart rate was significantly decreased after commencing both carvedilol (70.2 +/- 5.2 bpm) and nebivolol (64.9 +/- 3.9 bpm) treatments compared to placebo (78.8 +/- 5.2 bpm) (p<0.05). Both carvedilol (133.8 +/- 9/86.6 +/- 8.6 mmHg) and nebivolol (134 +/- 8.7/85.6 +/- 7.4 mmHg) significantly decreased mean systolic and diastolic blood pressures compared to placebo (143.9 +/- 8.9/94.4 +/- 9.2 mmHg), respectively (p<0.05). However, there was no significant difference in decreasing either systolic or diastolic blood pressure between nebivolol and carvedilol therapies (p>0.05). No side effects were recorded during both carvedilol and nebivolol treatments. Conclusion: Although both carvedilol and nebivolol effectively decreased blood pressure compared to placebo, they showed similar efficacy for lowering blood pressure. (Anadolu Kardiyol Derg 2011; 11: 310-3)
Keywords: Hypertension; nebivolol; carvedilol; beta-blocker; DOUBLE-BLIND